A Theoretical Study for Designing Optical Multilayer Films Using NdF3/ ThF4 - Al-Assadi, Zainab I. (Iraqi Journal of Science, 2021)
An idea of a colored glaze is presented in this study to hide and dispose all the obstacles of using solar systems as facades integrated with buildings. This aim is achieved by designing multilayer optical interference filters by using Mat lab program . Appropriate dielectric materials, namely NdF3 of high refractive index (nH =1.6) and ThF4 of low refractive index (nL =1.5143) were employed. Quarter wave thicknesses of high (H) and low (L) refractive index were deposited on a microscopic slide substrate with n=1.513 and 550 nm design wavelength (l°). Two optical models were designed, which are Air//HL//glass and Air//LH//glass, for even numbers of layers (2-32 layers). The challenge in this study is to find the most efficient design which has lower solar reflectance (Rsol.) and higher solar transmittance (Tsol.) to raise the efficiency of the solar systems and, in parallel, obtain the colored reflection to achieve the esthetic appearance of the buildings integrated with the solar system facades. The Tsol. value was high (94-95 %), whereas the Rsol. was very low (4-5 %). Hence, the efficiency of the solar system was increased. The two optical models exhibited green color reflectance in the visible region. The first design, i.e. Air/HL/glass, showed higher values of Rvis. and the merit factor (M) than the second model, resulting in a higher potential of coloration. The first design requires fewer materials and layers, thus, it is more cost-effective as compared to the second one.